PENGARUH PROMOSI, PERSEPSI HARGA, INOVASI PRODUK TERHADAP KEPUTUSAN PEMBELIAN PADA PERUSAHAAN PRIMA COLLECTION DI BANTARGEDANG KOTA TASIKMALAYA - Arman Maulana; Budhi Wahyu Fitriadi; Arga Sutrisna (JISMA: Jurnal Ilmu Sosial, Manajemen, dan Akuntansi, 2022)
This study aim to determine the effect of promotion, price perception, product innovation on purchasing decisions at a prima collection company in bantargedang tasikmalaya city. The method used is quantity with survey approach. With a consumer sampel of 100 respondents. The data analysis tool uses multiple regression equations using SPSS 20 software. The results show that promotion has a good value, price perception has a fairly good value, product innovation has a good vakue, purchase decisions have a fairly good value. Simultaneously promotion, price perception, product innovation have a significant effect on purchasing decisions.